(untitled) (Research, Society and Development, 2022)
The study aims to analyze whether the length of stay in the emergency department before hospital admission is associated with delirium in the elderly. This is a systematic review carried out according to the Systematic Reviews and Meta-Analysis (PRISMA) guideline. The search was performed in PubMed, SCOPUS, Web of Science, CINAHAL and Google Scholar databases, in addition to a manual search of the reference lists of the selected articles. After analyzing the eligibility criteria, three studies were included and presented as prospective or retrospective cohort design and evaluated the relationship between incidence of delirium and length of stay of elderly patients in the Emergency Department. All study participants had a length of exposure to the emergency department greater than or equal to 8 hours before being referred for hospital admission. The study allows us to conclude that the prolonged stay of elderly patients in the Emergency Room or Emergency Department increases the risk of developing delirium.